Penerapan Teknik Scaffolding Untuk Mengatasi Kesulitan Belajar Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Sistem Persamaan Linear Dua Variabel - Agustiana Wijiastuti Wahyudi; Teguh Wibowo; Erni Puji Astuti (Universitas Katolik Widya Karya Malang, 2023)
This study aims to describe the application of the scaffolding technique given by the teacher to overcome students' learning difficulties in solving word problems in the material of a system of two-variable linear equations. This type of research is case study research. The subjects of this study were 36 grade 8 students of junior high school. Subject taking using purposive sampling technique. The data collection technique uses the Learning Implementation Plan (RPP) instrument, syllabus, interviews, field notes, and documentation, each of which has been tried out and has met the validation requirements by the validator. The data analysis technique used is the process of data reduction, the process of presenting data, the process of drawing conclusions. After being given the scaffolding technique in each group, it was found that students were able to complete the test with good and correct completion steps. Students are able to determine variables and mathematical models correctly. In addition, students are also able to explain the steps of solving well.